2015
DOI: 10.5539/gjhs.v7n7p114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dust Storm on the Microbial Quality of Ambient Air in Sanandaj: A City Located in the West of Iran

Abstract: Background and Aims:The presence of pathogenic microorganisms in the dust storm can cause diseases such as Asthma, Pneumonia, and respiratory infections. The aim of this study was to determine the relationship between air-borne particles with airborne microorganisms in normal and dusty days in Sanandaj, a city located in the west of Iran.Materials and Methods:Air sampling was conducted during the normal and dusty days through Andersen single-stage impactor (28.3 L/min) for 2.5 min. Air particles concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…The most abundant of bacteria observed in the dust particles were Bacillus spp. 42, 55, 56 , Staphylococcus spp., Streptomyces spp., Micrococcus spp. 56 and Escherichia coli 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most abundant of bacteria observed in the dust particles were Bacillus spp. 42, 55, 56 , Staphylococcus spp., Streptomyces spp., Micrococcus spp. 56 and Escherichia coli 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, most types of fungi were ( Mycosporium spp. 55 Penicillium , Aspergillus flavus , Cladosporium , Alternaria , Rhizopus , and Cladosporium ) 46, 47 , C. albicans 42 . The pollen grains caused allergies, identified from dust storms, in descending order, included Chenopodiaceous , Graminea , Pine , Artemisia , Palmae , Olea , and Typha 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports from the countries nearby the KSA such as Jordan [21], Qatar [18], Egypt [29], Turkey [30], and Iran [31] have reported Cladosporium as the most predominant dematiaceous fungi. This coincides with our research which showed that at a percentage of 15.8%, Cladosporium are frequently isolated from the air and soil.…”
Section: Discussionmentioning
confidence: 99%
“…2016 ) Bacillus spp. Mycosporium spp Arabian dust Iran Culture dependent Human ( Nourmoradi et al. 2015 ) Bacillus; Streptococcus; Lactococcus; Anoxybacillus; Corynebacterium; Brevundimonas; Paracoccus; Sphingomonas; Methylobacterium; Caulobacter Aspergillus spp.…”
Section: Perspectivesmentioning
confidence: 99%